2020 rankings for US PharmD programs, research, and overall quality - Lisa Lebovitz; Kimberly K. Daugherty; Margarita V. DiVall; Eric G. Boyce; Michael Rudolph (Elsevier, 2022)
Background: US News and World Report (USNWR) publishes well-known rankings of graduate health programs. Medicine and nursing are ranked with weighted metrics using multiple criteria, and medical schools are ranked separately according to their focus (research or primary care). USNWR pharmacy school rankings are based on a single-question peer perception survey. Objective: The objective of this study was to develop a simple, transparent framework to rank US colleges and schools of pharmacy in overall quality and separately based on program quality and research quality, using data that are readily available to the academy. Methods: Data for three education quality and four research quality metrics were obtained for 2020. Each metric was standardized and ranked, and then each set was summed to determine separate ranks for education and research. Education and research scores were combined using equal weights to provide a single rank for overall quality. A sensitivity analysis was performed to determine the effect of assigning higher proportionate value to education, similar to USNWR medical school rankings. Results: Distinct ranks were produced for education, research, overall (education: research) 50:50, and overall 60:40. Sensitivity analysis suggests the more disproportionately the education and research factors are weighted, the more ranks change. Mid-ranked schools were most impacted when weightings changed due to relative strength in one factor and relative weakness in the other. When weighted 60:40, nine (7%) mid-ranked programs improved in rank, while 11 (11%) worsened in rank compared to the 50:50 model. Conclusion: Separately ranking education and research can highlight the diverse strengths of pharmacy schools. The proposed model is based on easily obtainable data and is easily reproducible, allowing for annual rankings. These rankings may be used by PharmD and PhD applicants when selecting schools and by pharmacy schools to benchmark true and aspirational peers.